Perbedaan Self-Efficacy Pencegahan Hipertensi Sebelum dan Sesudah Diberikan Edukasi Menggunakan Workbook pada Tenaga Kependidikan Kesehatan pada Salah Satu Perguruan Tinggi di Jawa Barat - Ristina Mirwanti; Melinda Ardian Dwi Cahya; Aan Nuraeni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
There are many health education methods, most of which do not involve the participants actively. Workbooks are educational media that encourage a person's active role and are expected to increase self-efficacy, where self-efficacy itself is a predictor of self-care management behavior. This study aimed to identify differences in hypertension prevention's self-efficacy before and after health education using a workbook. This study used a quasi-experimental method with a pre-post-test design with a control group. This study's population was teaching staff in two health faculties at one of the universities in West Java, Indonesia. The sample was determined using the convenience sampling technique and obtained 24 respondents divided into the control and intervention groups. Data collection using the instrument